FAKTOR-FAKTOR KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN - Median Wilestari; Diana Syafira Sidik (AKRUAL : Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of Dividend Policy, Sales and Liquidity Policy on Firm Value. The sample used in this study are industrial sector companies that are listed on the Indonesia Stock Exchange and issue financial reports and regularly distribute dividends in 2016-2020, so 35 samples were obtained using the purposive sampling method. By using panel data regression analysis method, the results of this study indicate that dividend and liquidity policies have a significant positive effect on firm value when the DPR and CR values ​​increase, it will affect the increase in firm value, while the sales policy variable as measured by net profit margin shows no significant effect. the value of the company, meaning that when the variable fluctuates, it will not affect the increase or decrease in the value of the company. The stock position of the sample company is in an overvalued position where the recommended investment decision is to sell shares.